2016
DOI: 10.4103/0972-9941.158154
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of complications in laparoscopic urology at a mid-volume institution using standardized criteria: Experience of 1023 cases including learning curve in 9 years

Abstract: AIM:To evaluate the laparoscopic operations performed in our department according to the modified Clavien classification system of complications.MATERIALS AND METHODS:Between September, 2005 and February, 2014, a total of 1023 laparoscopic cases were performed. This period was divided into three terms (Terms 1, 2 and 3 consisting of 38, 32 and 32 months, respectively). According to the European Scoring System (ESS), easy (E), slightly difficult (SD), fairly difficult (FD), difficult (D), very difficult (VD) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…The overall complication rate (13.4%) was within accepted international standards that were performed in single or multi-institutional settings. [ 4 6 12 13 14 15 ] The increasing experience that developed by a single surgeon in this study showed a significant reduction in the incidence of complications with experience. The complication rate was 19.8% during the first 4 years of the study.…”
Section: Discussionmentioning
confidence: 73%
“…The overall complication rate (13.4%) was within accepted international standards that were performed in single or multi-institutional settings. [ 4 6 12 13 14 15 ] The increasing experience that developed by a single surgeon in this study showed a significant reduction in the incidence of complications with experience. The complication rate was 19.8% during the first 4 years of the study.…”
Section: Discussionmentioning
confidence: 73%
“…Other authors also report that transoperative bleeding is more frequently associated with nephrectomy because of lithiasis and renal tumor, nephroureterectomy and tumorectomy; results that coincide with this study. (18,20) Infectious complications were the most frequent, fever without focalization prevailed which was treated with antibiotic therapy in 17 (3.9%) patients and two (0.5%) with general measures. Liapis et al (15) (15) report two retroperitoneal abscesses drained surgically.…”
Section: Discussionmentioning
confidence: 99%
“…(3,9,15) In this study, grade II complications prevailed, as in other investigations that report a prevalence of minor complications (grade I, II). (3,15,20) Al-Otaibi et al (18) reported two grade V (0.48%) complications, one as the result of the perforation of the duodenum complicated with septic shock and another due to pulmonary thromboembolism. Sanli et al (20) deaths (0.49%).…”
Section: Discussionmentioning
confidence: 99%
“…Many complications have been published in the urology field since the definition of laparoscopic surgery. Complications of laparoscopic urological procedures rates are variable and were given in the literature from 4.4% to 23.1% [6][7][8][9][10][11][12][13][14][15][16]. In their early laparoscopic experience, Parra et al [5] reported their rate of complications 15%.…”
Section: Discussionmentioning
confidence: 99%